Isolation and Characterization of Triclosan Resistant Bacteria from Sewage Water Sample - Gupta, Sunaina Ranjan; Sachan, Ashish (Journal of Neonatal Surgery, 2025)
The widespread use of triclosan, an antimicrobial agent, commonly found in household products, raised concern regarding its potential to select for resistant bacteria in environmental settings. Despite this, triclosan is still a useful drug for treating several infectious organisms. Examining microorganisms that have become resistant to triclosan is the goal of this investigation. Sewage water and hospital drainage water was collected, much possibility of finding resistant bacteria there. In order to comprehend adaptation processes of microorganisms, it’s essential to isolate and characterize bacteria resistant to triclosan. The process of isolation entails acquiring bacterial strains from a variety of environmental sources, sewage water samples, inoculating them with triclosan at varying dilutions, and then incubating them for one week at 370C in a medium containing mineral salts. To get pure isolation cultures, were sub-cultured on nutrient agar medium, physical characteristics, morphological structures, growth patterns, and their chemical characteristics were used for characterization. To identify the precise genetic factors causing triclosan resistance, genomic analysis will also be carried out. The results revealed significant presence of triclosan-resistant bacteria, isolates showed varying levels of resistance to triclosan, with some exhibiting cross-resistance to other antibiotics, suggesting the potential for multi-drug resistance. It have consequences for public health regulations and the creation of substitute antimicrobial tactics in addition to advancing our scientific knowledge of triclosan resistance. We can more effectively negotiate the complicated terrain of antibiotic resistance and strive towards long term solutions by clarifying the complex interaction between bacteria and triclosan.